The Decline of Elementary School Students' Attitudinal Values - Hafidhi, Nur Muhammad; Hanafi, Yusuf; Syamsul Hadi; Kusumaningrum, Shirly Rizki; Indra Dewi, Radeni Sukma (LPPM Undiksha, 2024)
The deterioration of primary school students' attitudes in the modern era is a significant concern, especially in the context of character education. This study aims to analyze the phenomenon of the decline in the value of attitude of elementary school students and identify the factors that contribute to the decrease in the value of attitude of students in one elementary school. This research used a qualitative case study approach, with the research subjects consisting of a grade V teacher and students who experienced an attitudinal slump. Data were collected through observation and structured interviews and then analyzed using the interactive cycle analysis method. The instruments used were observation and interview sheets. The results showed that some students experienced attitudinal deterioration marked by dishonest behavior, indiscipline, and physical and verbal bullying. It can be concluded that the role of schools and parents is crucial in overcoming the problem of students' attitudinal deterioration. Schools should integrate character education into the curriculum and implement Social-Emotional Learning programs to help students manage emotions and build empathy. The findings of this study emphasize that the role of schools is not only limited to academic education but also character education, which needs to be implemented through a curriculum that emphasizes moral values and social-emotional learning.